Marine Physiology Down East: The Story of the Mt. Desert Island Biological Laboratory - Evans, David H. (Perspectives in Physiology, 2015)
This volume offers a comprehensive history of the Mount Desert Island Biological Laboratory (MDIBL), one of the major marine laboratories in the United States and a leader in using marine organisms to study fundamental physiological concepts. Beginning with its founding as the Harpswell Laboratory of Tufts University in 1898, David H. Evans follows its evolution from a teaching facility to a research center for distinguished renal and epithelial physiologists. He also describes how it became the site of major advances in cytokinesis, regeneration, cardiac and vascular physiology, hepatic physiology, endocrinology and toxicology, as well as studies of the comparative physiology of marine organisms. Fundamental physiological concepts in the context of the discoveries made at the MDIBL are explained, and the social and administrative history of this renowned facility is described.